Skopas of Paros and his World: Presentation of a Proceedings volume on Ancient Classical Art - Katsonopoulou, Dora (Actual Problems of Theory and History of Art, 2015)
The paper briefly discusses the contents of a recent publication of the Institute for the Archaeology of Paros and the Cyclades dedicated to one of the most renowned sculptors of Classical Greece, Skopas from the island of Paros. The volume entitled Skopas of Paros and his World, edited by the Institute’s President Dora Katsonopoulou and Andrew Stewart of Berkeley University, is the third in a series of books published by the Institute under the international title Paros, and constitutes the only collective volume ever published about this famous Greek sculptor. The 34 scholarly papers of the volume are arranged into four parts as follows. Part I entitled Skopas of Paros and Earlier Parian Sculpture, includes 8 studies on the sculptor’s personality and work, and his relationship to the island and its previous sculptural output. Part II entitled Skopas the Architect, contains 9 papers on the artist’s architectural projects and Part III entitled Skopas the Sculptor, includes 12 papers on his art and the statues he created for various cities of the ancient world in the course of his long career. Finally, Part IV entitled The Impact of Skopas’ Work, contains 5 papers on the influence that the sculptor’s art exerted over the ancient world.